Virus-like particles activate type I interferon pathways to facilitate post-exposure protection against Ebola virus infection. - Natarajan Ayithan; Steven B Bradfute; Scott M Anthony; Kelly S Stuthman; Sina Bavari; Mike Bray; Keiko Ozato (PLoS ONE)
Ebola virus (EBOV) causes a severe hemorrhagic disease with high fatality. Virus-like particles (VLPs) are a promising vaccine candidate against EBOV. We recently showed that VLPs protect mice from lethal EBOV infection when given before or after viral infection. To elucidate pathways through which VLPs confer post-exposure protection, we investigated the role of type I interferon (IFN) signaling. We found that VLPs lead to accelerated induction of IFN stimulated genes (ISGs) in liver and spleen of wild type mice, but not in Ifnar-/- mice. Accordingly, EBOV infected Ifnar-/- mice, unlike wild type mice succumbed to death even after VLP treatment. The ISGs induced in wild type mice included anti-viral proteins and negative feedback factors known to restrict viral replication and excessive inflammatory responses. Importantly, proinflammatory cytokine/chemokine expression was much higher in WT mice without VLPs than mice treated with VLPs. In EBOV infected Ifnar-/- mice, however, uninhibited viral replication and elevated proinflammatory factor expression ensued, irrespective of VLP treatment, supporting the view that type I IFN signaling helps to limit viral replication and attenuate inflammatory responses. Further analyses showed that VLP protection requires the transcription factor, IRF8 known to amplify type I IFN signaling in dendritic cells and macrophages, the probable sites of initial EBOV infection. Together, this study indicates that VLPs afford post-exposure protection by promoting expeditious initiation of type I IFN signaling in the host.